Hospitalizations among World Trade Center Health Registry Enrollees Who Were under 18 Years of Age on 9/11, 2001–2016 - Gargano, Lisa M. (Int J Environ Res Public Health, 2021)
Much of the literature on hospitalizations post-September 11, 2001 (9/11) focuses on adults but little is known about post-9/11 hospitalizations among children. Data for World Trade Center Health Registry enrollees who were under 18-years old on 9/11 were linked to New York State hospitalization data to identify hospitalizations from enrollment (2003–2004) to December 31, 2016. Logistic regression was used to analyze factors associated with hospitalization. Of the 3151 enrollees under age 18 on 9/11, 243 (7.7%) had at least one 9/11-related physical health hospitalization and 279 (8.9%) had at least one 9/11-related mental health hospitalization. Individuals of non-White race, those living in New York City Housing Authority housing, those exposed to the dust cloud on 9/11, and those with probable 9/11-related PTSD symptoms were more likely to be hospitalized for a 9/11-related physical health condition. Older age and having probable 9/11-related PTSD symptoms at baseline were associated with being hospitalized for a 9/11-related mental health condition. Dust cloud exposure on 9/11 and PTSD symptoms were associated with hospitalizations among those exposed to 9/11 as children. Racial minorities and children living in public housing were at greater risk of hospitalization. Continued monitoring of this population and understanding the interplay of socioeconomic factors and disaster exposure will be important to understanding the long-term effects of 9/11.